Repetition of al-Ma’ and Ma’ in Quranic context: meanings and intents - Nurul Mukminah Zainan Nazri; Latifah Abdul Majid; Wan Nasyrudin Wan Abdullah (Pusat Kelestarian Turath Islami, Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2017)
Repetition of words and verses in the Quran is among the miracle aspects of the Quran. It reveals the eloquence of the Quran as the Quran only contains pertinent repetition hence, preserves it from abhorred repetition. Among the word that is mentioned repeatedly is the word al-ma’ or ma’. However, the word is mentioned repeatedly in different context. The two words literally mean water but due to the different context, the real meaning of the words must be understood according to their respective context. The word al-ma’ or ma’ in the same context refers to the same meaning but repetition of each context in different syles have certain intents. For this study, special focus is given only to seven context because there is repetition of verses according to those context which justifies the study on the intent of repetition. This study is a qualitative study and the approach is content analysis. Data were collected through content and document analysis upon which data were analyzed thematically using descriptive and analytical methods. Results demonstrate that the word al-ma’and ma’ in seven context refers to different meaning which are rainwater, drink, disaster, creation of human being, place, water in paradise and hellfire and analogy. Repetition in each context also has certain intents. The implication of the study establishes that repetition of the word al-ma’ or ma’ in the Quran proves the Quranic miracle in terms of the eloquence which cannot be disputed since the Quran is the only miracle which last forever until the Day of al-Qiyamah.